Sasando Battle Arena sebagai Media Pembelajaran Musik Gereja Berbasis Digital: Uji Coba pada Mahasiswa Program Studi Musik Gereja Sekolah Tinggi Teologi Kristus Alfa Omega - Trianus Homklom; Teguh Supriyanto; Wahyu Lestari (STT Kristus Alfa Omega, 2026)
Church music education in Indonesia generally still relies on conventional approaches with minimal use of digital technology, making it less relevant for younger generations. At the same time, traditional instruments such as Sasando from East Nusa Tenggara are rarely integrated into church music curricula, despite their significant potential as a contextually meaningful liturgical medium. This study aims to examine the effectiveness of the Sasando Battle Arena educational game as a digital-based medium for church music learning among students of the Church Music Study Program at STT Kristus Alfa Omega Semarang. A mixed methods approach was employed: quantitative through testing Sasando Battle Arena on 24 students measuring scores, accuracy, and response time; and qualitative through theological-aesthetic analysis using interviews and observation. Results showed an average score of 86.42 and an accuracy rate of 74.29%, with female students achieving higher accuracy (77.78%). These findings imply that gamification based on traditional instruments has strong potential as a participatory, contextual, and relevant model for church music education in theological learning contexts.